Pengaruh Professionalism, Realibility, Attitudes, Accessibility, Service Recovery Dan Servicescape Terhadap Brand Image Destinasi Wisata Luak Gadang Bukik Baka Park Kamang Hilia - Silvy Nezi Azwita; Eddi Novra (Jurnal Penelitian Multidisiplin, 2025)
This study examines the influence of factors affecting the brand image of Bukik Baka Park tourist destination in Kanagarian Kamang Hilia, Agam Regency. This research uses a descriptive method with a quantitative approach and uses SEM-PLS to analyze data collected through questionnaires. The results showed that of the six independent variables tested, namely professionalism, reliability, attitudes, accessibility, service recovery, and servicescape, there were two variables that had a significant influence on the brand image of Bukik Baka Park tourist destination, namely attitudes and servicescape. These findings indicate that tourist attitudes towards the tourist destination and the quality of the physical environment of the tourist destination have a strong influence on brand image. This study recommends that the managers of Bukik Baka Park tourist destination focus on efforts to improve positive tourist attitudes and improve the quality of servicescape to enhance brand image and attract more tourists.